First Report on Fetal Cerebral Polyglucosan Bodies in Mucopolysaccharidosis Type VII - Hazim Kadhim; Valérie Segers; Catheline Vilain; Julie Désir; Nicky D'Haene (Hindawi Limited, 2017)
We report on the detection of discordant inclusions in the brain of a 25-week female fetus with a very rare lysosomal storage disease, namely, Sly disease (mucopolysaccharidosis (MPS) type VII), presenting with nonimmune hydrops fetalis. Besides vacuolated neurons, we found abundant deposition of polyglucosan bodies (PGBs) in the developing brain of this fetus in whom MPS-VII was corroborated by lysosomal beta-glucuronidase-deficiency detected in fetal blood and fetal skin-fibroblasts and by the presence of a heterozygous pathogenic variant in the GUSB gene in the mother. Fetal/neonatal metabolic disorders with PGB-deposition are extremely rare (particularly in relation to CNS involvement) and include almost exclusively subtypes of glycogenosis (types IV and VII). The accumulation of PGBs (particularly in the fetal brain) has so far not been depicted in Sly disease. This is the first report on such "aberrant" association. Besides, the detection of these CNS inclusions at such an early developmental stage is remarkably unique.